Effect of local massage on prevention and treatment of intra-arterial polymethyl methacrylate embolism complications: An experimental animal study - Fangfei Nie; Hongbin Xie (Chinese Journal of Plastic and Reconstructive Surgery, 2022)
Background: Massage is generally believed to be a simple and effective method for preventing necrosis when intravascular injection emboli are suspected. Due to its good dispersive properties, polymethyl methacrylate (PMMA) was used as the test filler. The main purpose of this study was to observe whether local massage as a simple remedial measure can promote the diffusion of filler and reduce the necrosis rate for intra-arterial embolism. Methods: Rabbit ears with the central ear artery (CEA) main trunk totally or segmentally obstructed 5 ​min after PMMA injection were studied. In order to simulate the massage effect of the fingers, the massage group was treated with a small beauty massage bar with a fixed vibration frequency along the direction of the blood flow. CEA blood flow and skin lesions were also analyzed. Results: The baseline data were similar between the control and massage groups. Compared to the control group, the recanalization rate of the CEA trunk in the treatment group increased significantly after massage. However, there was no significant difference in the visible rate of transparent embolus on the 1st day after treatment, nor in the necrosis degree or area of soft tissue damage on the 7th day after treatment. Further analysis showed that massage tended to have a positive effect on segmentally obstructed cases at 5 ​min after injection but a negative effect on totally obstructed ears at 5 ​min. Conclusion: Local massage cannot reduce the complications of tissue necrosis after intra-arterial PMMA injection. Prevention is key to reducing complications.